PENGURUSAN FESTIVAL FLORIA DIRAJA PUTRAJAYA - NUR SAKINAH, MOHD (Universiti Malaysia Sarawak, (UNIMAS), 2016)
This study focuses on the management of Royal Floria Putrajaya Festival. This festival is organized by the Putrajaya Corporation and conducted by Putrajaya Floria Sdn. Bhd. Anjung Floria, Precinct 4. This research aims to identify the concept and assessing the management of the Royal Floria Putrajaya Festival. While the method used is qualitative methodology which is observation and interviews. Informants were interviewed consisted of Mr. Haris Fazilah Ahmad, Abu Darim Roziyanti Mrs. and Mrs. Nabilah Rahman who are most experienced and professional in directly involved in this festival. Research findings shows how the researcher had found the systematic management of the initial setup, during and closing events in Floria Diraja Putrajaya Festival.